77 years of uninterrupted agricultural research in Suceava - Enea, I.C.; Negrușeri, N.; Bodea, D. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2024)
In 1946, by decision no. 1933 of the Ministry of Agriculture, the first agricultural research unit in the northern part of Moldova (the Suceava Experimental Agricultural Station, currently the Suceava Agricultural Research and Development Station) was established, as a necessity for the development of agriculture in Bucovina. After three years of operation in the submontane area from Ilisesti (19 km from Suceava), by decision no. 564249 of August 24 of the same ministry, the resort was transferred to Suceava. The area where the cantonment is located is individualized by specific pedoclimatic conditions, characterized by thermal restrictions, the non-uniformity of the hydrological regime — from insufficient to excessive — and by a great diversity of soil types, from soils with low fertility to those with good fertility. The consequence of this ecological diversity was, from the beginning, the need to diversify the concern related to research activity in response to solving the main problems of agriculture in the Suceava Plateau. If in the year of establishment (1946) the concerns were directed towards the cultivation of potatoes, meadows and fodder plants, over time it can be seen by following the evolution of concerns and the way of achieving the basic objectives of agricultural research, in Suceava, a continuous expansion of the problem areas addressed as well as the amplification of their complexity.